PENGEMBANGAN MATERI AJAR TEKS CERPEN BERBANTUAN VIDEO MULTIMEDIA PADA SISWA KELAS XI MAS AL WASHLIYAH MEDAN - Halimatussakdiah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study intends to analyze the process, form, and feasibility of developing teaching materials for short story texts using multimedia video assistance for grade XI students of MAS AL WASHLIYAH using the 4D model. However, this study is limited to the development stage due to limited time and conditions. The validation stage involved material and design expert lecturers to evaluate the feasibility of the material and design. Data collection techniques used questionnaires and instruments. The data were analyzed using quantitative descriptive analysis. The results showed that the product of the development of short story text teaching materials using multimedia video assistance obtained research results with